1982
DOI: 10.1002/food.19820260311
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of sausage as prepared with alginate and alginate casings

Abstract: Fresh buffalo sausage was prepared with 3 % sodium alginate, 0.5 ' 7" sodium pyrophosphate or 3 % alginate + 0.5 76 sodium pyrophosphate and stuffed in natural mutton casing or alginate casing. All samples were stored at +4 "C and analysed.Addition of 3 :; alginate was more effective in protection of sausages from drying, increased markedly the water holding capacity (WHC), increased considerably the cooking yield of sausage and plasticity when compared with 0.5 % pyrophosphate samples. During storage at +4 "C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1986
1986
2014
2014

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 3 publications
0
3
0
Order By: Relevance
“…Studies of sensory attributes of precooked, calcium alginate-coated pork patties (Wanstedt et al,198 1) indicated that a calcium alginate coating was useful in preventing warmed-over flavor of precooked pork. Alginates have also been incorporated into sausage products, for texture modification, and used as sausage casings (Abd El-Baki et al, 1981). However, this study mentioned no use of a calcium ion source.…”
Section: Introductionmentioning
confidence: 97%
“…Studies of sensory attributes of precooked, calcium alginate-coated pork patties (Wanstedt et al,198 1) indicated that a calcium alginate coating was useful in preventing warmed-over flavor of precooked pork. Alginates have also been incorporated into sausage products, for texture modification, and used as sausage casings (Abd El-Baki et al, 1981). However, this study mentioned no use of a calcium ion source.…”
Section: Introductionmentioning
confidence: 97%
“…Alginates have been incorporated into sausage products, for texture modification (Abd El-Baki et al, 1981). An important property of algin/calcium restructured meat products is their ability to achieve and retain shape and acceptable appearance in the raw refrigerated condition (Means and Schmidt, 1986) and this property is an advantage over items which are manufactured using conventional restructuring technology (addition of salts and phosphates), which bind only in the cooked state.…”
Section: Cold-set Binding Systemmentioning
confidence: 99%
“…Alginate is an anionic polysaccharide composed of guluronic and mannuronic acids. Because of its excellent gelation and water-holding properties, alginate is used in many food products such as breading mix, dairy foods, sauces, and processed meats (McDowell, 1975; Abd El-Baki et al, 1981). Recently, we reported on the use of calcium alginate as a meat binding agent in restructured meats (Means and Schmidt, 1986; Means et al, 1987).…”
Section: Introductionmentioning
confidence: 99%